GENDER AND ETHICS COMMITTEES: WHERE’S THE ‘DIFFERENT VOICE’? - Dickenson, Donna (Bioethics, 2006)
Prominent international and national ethics commissions such as the UNESCO International Bioethics Committee rarely achieve anything remotely resembling gender equality, although local research and clinical ethics committees are somewhat more egalitarian. Under-representation of women is particularly troubling when the subject matter of modern bioethics so disproportionately concerns women’s bodies, and when such committees claim to derive ‘universal’ standards. Are women missing from many ethics committees because of relatively straightforward, if discriminatory, demographic factors? Or are the methods of analysis and styles of ethics to which these bodies are committed somehow ‘anti-female’? It has been argued, for example, that there is a ‘different voice’ in ethical reasoning, not confined to women but more representative of female experience. Similarly, some feminist writers, such as Evelyn Fox Keller and Donna Haraway, have asked difficult epistemological questions about the dominant ‘masculine paradigm’ in science. Perhaps the dominant paradigm in ethics committee deliberation is similarly gendered? This article provides a preliminary survey of women’s representation on ethics committees in eastern and western Europe, a critical analysis of the supposed ‘masculinism’ of the principlist approach, and a case example in which a ‘different voice’ did indeed make a difference.